Effect of environmental acidification on hepatic tissue A1AT kinetics of fish during acclimation - Shobharani, P; Bhaskar, M; Madhuri, E; Govindappa, S (Indian Journal of Fisheries, 2011)
Fresh water fish, Tilapia mossambica (Peters) were subjected to acclimation tosublethal acidic (pH 4.0) water and its impact on the hepatic tissue Alanine AminoTransferase (A1AT) activitiy was studied. The studies on substrate dependencyof the enzyme showed significant increase in the activity levels of the enzyme inacclimated animals over the controls at all the substrate concentrations. Themaximum per cent increase after acclimation was 25 p moles of substrateconcentration. The pH dependency analysis recorded significant elevation in theactivity level of the enzyme in acclimated tissues over the control at all the pHvalues studied. The temperaSHre dependency studies revealed maximum activityof the enzyme in control tissue at 30Â°C, whereas it was 40Â°C in experimental. Itcan be concluded that the process of acclimation to acidic environment inducesadaptive mechanisms as a compensatory measure into enzymatic activities asevidenced by the activity of A1AT which in turn provides resistance to fish leadingto successfull survival in extreme acidic waters